Handling Troubled Students with Death Education Program (A Case Study of Madrasah Aliyah Plus Nururrohmah Kebumen, Indonesia) - Azam Syukur Rahmatullah (TSAQAFAH, 2021)
This study discusses the solution that is not widely applied to settle troubled students in Indonesia. Generally, the resolving applied is based on the cognitive aspect. The spiritual element is less accustomed to and less cultivated. Suggestion method, physical punishment method, and lecture method are widely used to help heal and enlighten troubled students. However, one religious school in Kebumen, Indonesia, still applies a different approach and strategy from the other schools and Madrasah (Islamic schools). Madrasah Aliyah Plus Nururohmah implements cognitive to enrich and cultivate the death education program. As a media which changes the misbehaving students to be good, and have mature behavior and mindset. Several stages were conducted, including demonstration of death, muhasabah graveyard, and going to some funerals, in which there was counseling in-between. Those stages aim to help fix, enrich, enlighten, and lead the misbehaving students to have good and positive attitudes.